Inter-Layer Interference (ILI) Suppression in Dual-Layer Bit-Patterned Magnetic Recording Systems - Natthakan Rueangnetr; Santi Koonkarnkhai; Simon John Greaves; Chanon Warisarn (My University, 2025)
Dual-layer bit-patterned magnetic recording (DL-BPMR) systems are promising for achieving higher areal densities. However, they face significant challenges, including inter-symbol interference (ISI), inter-track interference (ITI), and inter-layer interference (ILI). To address these issues, this work proposes integrating a sum-soft-information (SSI) technique and an ITI suppression method to enhance detection reliability. The SSI technique is initially used to improve the reliability of the log-likelihood ratio for the bottom layer signal by leveraging the mutual information derived from a staggered array reader configuration. The enhanced data sequence from the bottom layer is subsequently utilized to suppress ILI by applying a weighting before it is subtracted from the top layer readback signals. Simulation results demonstrate that the proposed method significantly improves bit error rate (BER) performance compared to conventional single-layer and dual-layer BPMR systems, particularly at a user density of 4.0 Tb/in2, making it a promising approach for next-generation high-density magnetic recording.
Keywords: Cellular Automata and Applications; Magnetic properties of thin films; Advanced Data Storage Technologies